Plasma Venetoclax Concentrations in Patients with Acute Myeloid Leukemia Treated with CYP3A4 Inhibitors - Ayaka Otsukia; Masaki Kumondaia; Daisuke Kobayashia; Masafumi Kikuchia; b; c; †; Yugo Uekia; Yuji Satoa; Nagomi Hayashib; Ayaka Yagic; Yasushi Onishid; et al. (YAKUGAKU ZASSHI (Journal of the Pharmaceutical Society of Japan), 2024)
Venetoclax (VEN) is used in patients with acute myeloid leukemia (AML) and is primarily metabolized by CYP3A4, a major drug-metabolizing enzyme. Patients with AML simultaneously administered VEN and CYP3A4 inhibitors require a more appropriate management of drug-drug interactions (DDIs). Here, we report two cases of patients with AML (54-year-old man and 22-year-old woman) administrated VEN and CYP3A4 inhibitors, such as posaconazole, cyclosporine, or danazol. In the first case, we evaluated the appropriateness of timing for adjusting VEN dosage subsequent to the cessation of posaconazole. Consequently, modifying the VEN dosage in conjunction with the cessation of Posaconazole simultaneously may result in elevated plasma VEN levels. In the second case, plasma VEN concentrations were markedly elevated when co-administered with several CYP3A4 inhibitors. Additionally, in vitro assays were conducted for reverse translational studies to analyze CYP3A4 inhibition. CYP3A4 inhibition by combinatorial administration of cyclosporine A and danazol was demonstrated in vitro, which potentially explains the increasing plasma VEN concentrations observed in clinical settings. Although the acquisition of therapeutic effects is a major priority for patients, frequent therapeutic drug monitoring and dosage adjustments considering DDIs would be important factors in chemotherapy.